A tension insensitive PbS fiber temperature sensor based on Sagnac interferometer - 付兴虎 张江鹏 杨凯丽 董艳华 文建湘 付广伟 毕卫红 (Optoelectronics letters, 2017)
In this paper, a tension insensitive Pb S fiber temperature sensor based on Sagnac interferometer is proposed and demonstrated. The sensing mechanism of tension and temperature is analyzed. The relationships between the interference spectrum, temperature and tension are analyzed, respectively. The experimental temperature range is 36—70 °C. The experimental results show that the interference spectrum is red shifted, and its sensitivity is 53.89 pm/°C. In tension experiment, the tension range is 0—1 400 με. The experimental results show that there is no wavelength shift in the interference spectrum. The sensor is immune to tension cross-sensitivity compared with other sensors. It can be used for temperature testing in aerospace, chemistry and pharmacy.